2011
DOI: 10.1111/j.1365-2141.2011.08863.x
|View full text |Cite
|
Sign up to set email alerts
|

Promising therapy results for lymphoid malignancies in children with chromosomal breakage syndromes (Ataxia teleangiectasia or Nijmegen‐breakage syndrome): a retrospective survey

Abstract: Summary Children with chromosomal instability syndromes have an increased risk of developing lymphoma and leukaemia. The treatment of these malignancies is hampered by therapy‐associated toxicity and infectious complications. This retrospective analysis evaluated the therapy outcome of 38 children with Ataxia teleangiectasia or Nijmegen‐breakage syndrome with acute lymphoblastic leukaemia (ALL, n = 9), Non‐Hodgkin lymphoma (NHL, n = 28) and Hodgkin lymphoma (HL, n = 1). All patients with NHL or ALL were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 29 publications
(40 reference statements)
1
47
0
4
Order By: Relevance
“…[5][6][7][8]10,16,22,46 Our analysis showed that while approximately 50% of AT patients died from therapy-related toxicity, death from NHL and therapy-related complications was evenly distributed among NBS patients. In comparison, the NHL-BFM SG reported on 37 patients with chromosomal instability syndromes (AT and NBS) with 5-year EFS rates of 48%±12% for 16 patients with ALL/T-LBL (relapse/progression n=2; SML n=2; treatment-related death n=2; alive n=10) and 51%±16% for 21 patients with mature B-cell NHL (relapse/progression n=2; SML n=2; treatment-related death n=1; dead from underlying disorder n=4; alive n=12).…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…[5][6][7][8]10,16,22,46 Our analysis showed that while approximately 50% of AT patients died from therapy-related toxicity, death from NHL and therapy-related complications was evenly distributed among NBS patients. In comparison, the NHL-BFM SG reported on 37 patients with chromosomal instability syndromes (AT and NBS) with 5-year EFS rates of 48%±12% for 16 patients with ALL/T-LBL (relapse/progression n=2; SML n=2; treatment-related death n=2; alive n=10) and 51%±16% for 21 patients with mature B-cell NHL (relapse/progression n=2; SML n=2; treatment-related death n=1; dead from underlying disorder n=4; alive n=12).…”
mentioning
confidence: 75%
“…In comparison, the NHL-BFM SG reported on 37 patients with chromosomal instability syndromes (AT and NBS) with 5-year EFS rates of 48%±12% for 16 patients with ALL/T-LBL (relapse/progression n=2; SML n=2; treatment-related death n=2; alive n=10) and 51%±16% for 21 patients with mature B-cell NHL (relapse/progression n=2; SML n=2; treatment-related death n=1; dead from underlying disorder n=4; alive n=12). 6 Of our CMMRD patients, nearly 75% died, either from NHL or another SML. This extremely high mortality rate also confirms that CMMRD has to be diagnosed in a timely fashion to allow tumor surveillance, and that adapted chemotherapies are necessary to treat the different highly resistant childhood cancers occurring in this group of patients.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Children with ALL have a 5-year survival rate of more than 90 % (Bienemann et al 2011 ). It may well be that a proportion of the 10 % of children who do not survive are enriched for children with cancer-predisposing conditions that make them prone for comorbidity, second primary malignancies, and more severe toxic side effects of treatment.…”
Section: Rare Genetic Variants Predisposing To Childhood All: "Syndromentioning
confidence: 99%